Plays of Destruction - Myers, David (Intermédialités / Intermediality, 2007)
Here the author considers the possibility that aesthetic objects — stories, narratives, and other similar cognitive structures — verlay and disguise human experience in a manner that is only revealed during the peculiar distortions of play. Working from the notion of human play as an anti-aesthetic form, the author examines playful destructions in film — Groundhog Day (1993), Lola rennt (1998), and Memento (2000)—and other media forms that serve to undermine conventional time and space, and, during that process, reveal the fundamental mechanics of human experience and creation of self.